A Modified Anterior Approach to L 1 Vertebra: An Early Clinical Experience. Issue 4 (December 2017) - Kumar, Vishal; Dhatt, Sarvdeep S.; John, Rakesh
Abstract : Purpose: To study the results of a new surgical approach to the L1 vertebra which is a modified anterior approach and is extrapleural and retroperitoneal in nature. Materials and Methods: Five patients with fracture L1 vertebra underwent surgical decompression and stabilization via this modified anterior approach. In this approach, the L1 vertebra is approached anteriorly without invading the pleural cavity or the peritoneal cavity by gentle, blunt dissection (extrapleural and retroperitoneal approach) Results: No significant complications, especially pulmonary complications, were noted in any of the 5 cases. Conclusions: This modified anterior approach to L1 vertebra allows effective, circumferential decompression of the thoracolumbar spinal canal without the associated morbidity of the traditional anterior approach. However, comparative studies between the 2 approaches will be needed in the future to more accurately ascertain benefits of this approach.